The Effect of Abusive Supervision on Leadership Identification and Customer Orientation and Its Impact on Job Performance - Gazali, Gazali; Zainurrafiqi, Zainurrafiqi (Universitas Bangka Belitung, 2023)
Based on Social Identity Theory dan Conservation of Resources Theory, this study aims to examine the effect of Abusive Supervision on Leadership Identification and Customer Orientation, the effect of Leadership Identification on Job Performance, the effect of Customer Orientation on Job Performance, and the effect of Abusive Supervision on Job Performance. The type of research is Explanatory Research. The number of samples in this study were 200 salespeople at a retail store in Pamekasan Regency, Data collection using a questionnaire, with simple random sampling method. Data analysis using Structural Equation Model-AMOS. The results showed that: Abusive Supervision have a negative and significant effect on Leadership Identification, Abusive Supervision have a negative and significant effect on Customer Orientation, Leadership Identification have a positive and significant effect on Job Performance, and Customer Orientation have a positive and significant effect on Job Performance